(untitled) (Experimental biology, 2018)
The study of the involvement of miRNAs in the regulation of the expression of candidate genes of myocardial infarction and coronary heart disease will facilitate the development of new effective methods for noninvasive diagnosis of these diseases. Using the MirTarget program to determine the characteristics of the interaction of miRNA with mRNA, the following original results were obtained. The 183 genes involved in the development of MI, 35 genes were associated with 51 miRNAs in the 5’UTR, 53 genes with 94 miRNA in the CDS, and 37 genes with 50 miRNAs in the 3’UTR. 24 genes bind to only one miRNA were arranged in the 5’UTR, 36 genes in the CDS, and 24 genes in the 3’UTR. The remaining mRNAs of the genes involved in the development of MI were associated with two or more miRNAs. Nine genes under the control of miRNAs were bound in the 5’UTR, 21 genes in the CDS, and 15 in the 3’UTR. Most of the interactions occurred at the CDS site. The largest number of binding sites had the mRNA of the CXCR2 and FAIM2 genes in the 3’UTR. Only three genes had binding sites in all regions: AP3D1, GATA2, SEMA3F. MI candidate genes PDED4 was regulated by 13 miRNAs with free energy of binding miRNAs with mRNAs -144 kJ/mole; genes ILF3, GATA2 were regulated by five and three miRNAs respectively with the free energy of binding miRNAs with mRNAs -138 kJ/mole; genes TGFBR1 and AP3D1 were regulated by six and five miRNAs with free energy of binding miRNAs with mRNAs -136 kJ/mole and -140 kJ/mole respectively. The 174 genes participating in the development of IHD, 34 genes were associated with 43 miRNAs in the 5’UTR, 55 genes with 90 miRNAs in the CDS, and 35 genes with 53 miRNAs in the 3’UTR. Of them, 23 genes that bound to only one miRNA were located in the 5’UTR region, 34 genes in the CDS, and 19 genes in the 3’UTR. The mRNAs of genes involved in the development of IHD were associated with two or more miRNAs. Eight genes under the control of miRNAs were bound in the 5’UTR, 20 genes in the CDS, and 15 in the 3’UTR. The mRNA of the THRA gene in 5’UTR, the SMARCA4 gene in the CDS, and the LDLR gene in the 3’UTR had the largest number of interaction sites. The binding sites located at 5’UTR had the strongest interaction. Only two genes had binding sites in all sites: CTCF and F2RL3. IHD candidate genes SMARCA4, TGFB1 and DOCK7 were regulated by seven, five and two miRNAs with free energy of binding miRNAs with mRNAs -140 kJ/mole, -140 kJ/mole and -138 kJ/mole respectively. There were genes characteristic for only one subtype: myocardial infarction - ADRB1, ILF3, GATA2, TGFBR1, AP3D1; ischemic heart disease - SMARCA4, DOCK7, CELSR2, TRIB1. All of the above mentioned ассоциации miRNA с mRNA can be used as the promising markers of myocardial infarction and ischemic heart disease. Key words: miRNA, mRNA, myocardial infarction, ischemic heart disease, candidate genes.